2009
DOI: 10.1016/j.bbabio.2009.02.023
|View full text |Cite
|
Sign up to set email alerts
|

IF1, the endogenous regulator of the F1Fo-ATPsynthase, defines mitochondrial volume fraction in HeLa cells by regulating autophagy

Abstract: The protein IF1 limits mitochondrial ATP consumption when mitochondrial respiration is impaired by inhibiting the 'reverse' activity of the F(1)F(o)-ATPsynthase. We have found that IF1 also increases F(1)F(o)-ATPsynthase activity in respiring mitochondria, promoting its dimerization and increasing the density of mitochondrial cristae. We also noted that IF1 overexpression was associated with an increase in mitochondrial volume fraction that was conversely reduced when IF1 was knocked down using small interferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 52 publications
4
56
1
Order By: Relevance
“…IF1 Does Not Affect Mitochondria Morphology-Previous studies reported that knockdown of IF1 caused stimulation of autophagy, decrease in mitochondrial volume fraction in the cell, and decrease in cristae density in mitochondria (10,11,13,14). However, none of these were observed for IF1-KD cells with certainty in our study.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…IF1 Does Not Affect Mitochondria Morphology-Previous studies reported that knockdown of IF1 caused stimulation of autophagy, decrease in mitochondrial volume fraction in the cell, and decrease in cristae density in mitochondria (10,11,13,14). However, none of these were observed for IF1-KD cells with certainty in our study.…”
Section: Discussioncontrasting
confidence: 54%
“…When cells are deprived of oxygen and glucose, IF1-suppressed cells lose cellular ATP and die more rapidly than control cells, suggesting a role of IF1 in maintaining ATP concentration ([ATP]) in energy crises (9). Several groups reported that IF1 facilitates dimer formation of F o F 1 in the inner mitochondrial membranes (10 -12) and contributes to cristae formation (9,(13)(14)(15)(16)(17)(18). This profound effect of IF1 on mitochondrial morphology remains controversial (19,20).…”
mentioning
confidence: 99%
“…Although mitochondria can be engulfed non-selectively along with other cytosolic contents during bulk autophagy, 31 32,33 Similarly, knockdown of an inhibitor of the mammalian F 0 F 1 ATPsynthase, IF1, causes a dramatic reduction in mitochondrial mass that correlates with increased autophagic activity. 34 Depolarization of mitochondria with the uncoupler carbonyl cyanide m-chlorophenylhydrazone (CCCP) 35 or photo-irradiation 36 induces autophagic clearance of mammalian mitochondria while leaving other organelles such as peroxisomes intact. Recently, it has been reported that mitochondria carrying deleterious mutations in mtDNA can be selectively eliminated through mitophagy, 37 although additional activation of macroautophagy, such as rapamycin-mediated inhibition of TORC1, may be required for efficient clearance.…”
Section: Mitophagy As a Selective Form Of Autophagymentioning
confidence: 99%
“…For reasons explained above this strategy is less applicable to thicker specimens [222]. However, a "semi-3D" image can be created by collapsing multiple imagesections from a wide-field or confocal z-stack into a single 2D projection [224,261]. A more advanced strategy consists of calculating a 3D representation of the mitochondrial compartment from the z-stack and performing a 3D analysis of mitochondrial number, morphology (e.g.…”
Section: Interpretation Of Quantitative Data For Mitochondrial Morphomentioning
confidence: 99%
“…respect to mitochondrial content, the fractional cellular volume occupied by mitochondria has been measured based on fluorescence detection of mitoGFP and calcein blue in the cytosol [224]. Alternatively, we and others have developed procedures allowing systematic analysis of mitochondrial shape, number and mass using fluorescence microscopy images ( Table 2).…”
Section: Quantification Of Mitochondrial Morphology and Content Usingmentioning
confidence: 99%